The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00520-018-4189-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of psychological distress among Asian adolescents and young adults (AYA) cancer patients using the distress thermometer: a prospective, longitudinal study

Abstract: The DT is a useful screening tool for psychological distress in AYA cancer patients with clinically significant distress being identified in the early phases of the cancer journey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
44
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 33 publications
5
44
1
Order By: Relevance
“…The accompanied PL items have been used to ascertain key concerns that may have perpetuated distress. Problems that most contributed to distress include emotional issues (particularly worry) and insurance/financial challenges which evidenced the need to provide emotional and financial counseling; the more commonly endorsed physical symptoms associated with distress are fatigue and sleep, indicating necessity for education and further rehabilitation [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The accompanied PL items have been used to ascertain key concerns that may have perpetuated distress. Problems that most contributed to distress include emotional issues (particularly worry) and insurance/financial challenges which evidenced the need to provide emotional and financial counseling; the more commonly endorsed physical symptoms associated with distress are fatigue and sleep, indicating necessity for education and further rehabilitation [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously conducted a longitudinal assessment of symptom burden and distress in a cohort of AYA cancer patients. 13 In this article, the self-reported cognitive function of patients with non-CNS malignancies will be reported. Furthermore, CRCI-associated characteristics will be identified.…”
mentioning
confidence: 99%
“…However, the quality of life of AYA patients compared to the age-matched general population was also significantly lower after 2 years. Furthermore, Chan et al ( 2018 ) published a longitudinal study from the Asian region that examined the distress of AYA patients ( N = 65) in the first 6 months after diagnosis. They showed that there was a decrease in distress from the time of diagnosis to 6 months later.…”
Section: Introductionmentioning
confidence: 99%